EDUCATION IN PEDAGOGY - Mukhammadieva Khilola (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, first of all, work with the meanings, values, system of human relations, his emotional-volitional and reflexive spheres, with everything that allows a person to realize, evaluate and improve himself, while making conscience the main criterion for his own actions and deeds.